2021
DOI: 10.48550/arxiv.2107.13547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflation in Energy-Momentum Squared Gravity in Light of Planck2018

Abstract: We study cosmological dynamics of the energy-momentum squared gravity. By adding the squared of the matter field's energy-momentum tensor (ζ T 2 ) to the Einstein Hilbert action, we obtain the Einstein's field equations and study the conservation law. We show that the presence of ζ T 2 term, breaks the conservation of the energy-momentum tensor of the matter fields. However, an effective energy-momentum tensor in this model is conserved in time. By considering the FRW metric as the background, we find the Frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37] and references therein. In this regard, various modified theories of gravity have also been considered for inflationary cosmology in the hope that their predictions can better justify the observational data [38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37] and references therein. In this regard, various modified theories of gravity have also been considered for inflationary cosmology in the hope that their predictions can better justify the observational data [38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Such matter-geometry coupling explains different eras of the universe as well as the rotation curves of galaxies. Faraji et al [41] used Friedmann-Lemaitre-Robertson-Walker (FLRW) metric to observe the effect of coupling parameter and found that the range (0, 2.1 × 10 5 ] provides observationally viable inflationary model. Several remarkable results have also been obtained by using the Kuchowicz metric in this scenario [42].…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to note that in the framework of inflationary cosmology, the numerical analysis done on the perturbation parameters of the EMSG model has shown that it can be a viable potential candidate from the view of Planck2018 data[100]. Note that this does not mean that the modified gravity model at hand is problem-free.…”
mentioning
confidence: 99%